Banking union through Hungarian eyes: The MNB's assessment of a possible close cooperation - Kornél Kisgergely; Anikó Szombati (Magyar Nemzeti Bank, 2014)
Legislation laying down the institutional system of the Banking Union was finalised in April 2014. In accordance with the regulations, non-euro area Member States, including Hungary, may notify the ECB at any time if they wish to participate in the common system even before the euro is adopted. However, in its existing form, the single supervisory and crisis management mechanism has not achieved the initial goal, i.e. the separation of the stability of national banking systems and the fiscal capacity of Member States and the elimination of interdependencies. In addition, close cooperation implies weaker powers than those provided by actual membership, and the separation of central bank and supervisory functions carries risks in non-euro area countries. By contrast, the attraction of Banking Union membership lies in the opportunity to join a uniform European system, a wider analyst base and ultimately, the "ammunition" of the EUR 55 billion available for crisis management in comparison to the contributions coming solely from the Hungarian banking system. In October 2013, a single supervisory system integrated into the central bank was set up in Hungary, and the institutional system of the domestic resolution mechanism will be complete by the end of 2014. Therefore, until the actual launch of the Banking Union and the commencement of payments into the Resolution Fund in 2016, it is reasonable to put the decision to join on hold; indeed, such a decision should be made in light of several factors presented in this study.
Keywords: E58; F55; G21; G28; H12; H81; 330; Banking Union; close cooperation; SSM; SRM; financial crisis management